2020
DOI: 10.1038/s41598-020-74284-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of “re-positive” discharged COVID-19 pneumonia patients in Wuhan, China

Abstract: To analyze the clinical characteristics of re-positive discharged COVID-19 patients and find distinguishing markers. The demographic features, clinical symptoms, laboratory results, comorbidities, co-infections, treatments, illness severities and chest CT scan results of 267 patients were collected from 1st January to 15th February 2020. COVID-19 was diagnosed by RT-PCR. Clinical symptoms and nucleic acid test results were collected during the 14 days post-hospitalization quarantine. 30 out of 267 COVID-19 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…6,[9][10][11][12] However, a large number of cases showed no clinical symptoms and no change in laboratory indicators or imaging findings. 3,7,8,[13][14][15][16][17][18] Furthermore, the repositive patients tended to be younger, and most of them had mild disease symptoms at the first time of admission. 6,7,13,13,18,19 Compared with other discharged patients, no clinical characteristics or indicators were found to reliably predict the risk of a patient being repositive for SARS-CoV-2, nor were any specific drugs or treatments associated with SARS-CoV-2 reactivation.…”
Section: The Proportion and Clinical Characteristics Of Repositivementioning
confidence: 99%
See 2 more Smart Citations
“…6,[9][10][11][12] However, a large number of cases showed no clinical symptoms and no change in laboratory indicators or imaging findings. 3,7,8,[13][14][15][16][17][18] Furthermore, the repositive patients tended to be younger, and most of them had mild disease symptoms at the first time of admission. 6,7,13,13,18,19 Compared with other discharged patients, no clinical characteristics or indicators were found to reliably predict the risk of a patient being repositive for SARS-CoV-2, nor were any specific drugs or treatments associated with SARS-CoV-2 reactivation.…”
Section: The Proportion and Clinical Characteristics Of Repositivementioning
confidence: 99%
“…In the existing literature, strict isolation measures continue to be taken for discharged patients, and the chance of reexposure to the source of infection is very low, 7,8,11,11,17 which suggested that nucleic acid repositive patients are not reinfected with SARS-CoV-2, rather, it is likely that the virus was not completely cleared before the patients were discharged from hospital, and their previous nucleic acid test results were false negative. To ascertain why the nucleic acid results were false negative and SARS-CoV-2 is not easily cleared, the etiological and patient characteristics and laboratory tests should be analyzed in combination with the relevant literature.…”
Section: Cause Analysis For Recovered Covid-19 Patients With Reposimentioning
confidence: 99%
See 1 more Smart Citation
“…Although COVID‐19 reinfection was reported in a previous studies, the mechanism is not clear and it is still unknown if affected patients might present as carriers for the virus 5 …”
Section: Discussionmentioning
confidence: 97%
“…Although there is no direct study of the relationship between SPD and recurrent positive, several related studies have been found. A study of 30 recurrent positive patients from China showed that there was a significant difference in length of hospitalization between the recurrent positive group and the non-recurrent positive group [median and IQR 36 day (30-44) vs. 25 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)] [17]. Although the study did not directly point out the difference in SPD between the two groups, there was a direct correlation between length of stay and SPD (Chinese discharge criteria are described in "Study design and participants" section, the most important of which was the test of SARS-CoV-2 RNA negative) [14].…”
Section: Discussionmentioning
confidence: 99%